Pengaruh Struktur Modal, Ukuran Perusahaan Dan Pertumbuhan Penjualan Terhadap Nilai Perusahaan Pada Sektor Transportasi Dan Logistik Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2019- 2023 - Putri, Syalma Nabila; Maryati, Mari (Fakultas Ekonomi dan Bisnis Universitas Komputer Indonesia, 2024)
The purpose of this study is to determine the Influence of Capital Structure, Company Size and Sales Growth on Company Value in the Transportation and Logistics Sector Listed on the Indonesia Stock Exchange for the 2019-2023 Period. The analysis approach method used in this study is a quantitative approach with descriptive and verifiable methods. The sample used is the financial statements of 6 companies with the 2019-2023 period, which is 30 samples. The analysis used in this study is path analysis, classical assumption testing, correlation coefficient testing, determination coefficient testing and hypothesis testing using the SPSS application. The results of this study show that Capital Structure has a negative and significant effect on Company Value, Company Size has a negative and significant influence on Company Value, Sales Growth has a positive and insignificant effect on Company Value, Company Size has a significant negative effect on Capital Structure, Sales Growth has a positive and insignificant effect on Capital Structure. Capital Structure, Company Size and Sales Growth simultaneously have a significant positive effect on the Company's Value.